Ambient Temperature Stable, Scalable COVID‐19 Polymer Particle Vaccines Induce Protective Immunity. Issue 3 (10th November 2021) - Chen, Shuxiong; Evert, Benjamin; Adeniyi, Adetayo; Salla‐Martret, Mercè; Lua, Linda H.‐L.; Ozberk, Victoria; Pandey, Manisha; Good, Michael F.; Suhrbier, Andreas; Halfmann, Peter; Kawaoka, Yoshihiro; Rehm, Bernd H. A.
Abstract: There is an unmet need for safe and effective severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccines that are stable and can be cost‐effectively produced at large scale. Here, a biopolymer particle (BP) vaccine technology that can be quickly adapted to new and emerging variants of SARS‐CoV‐2 is used. Coronavirus antigen‐coated BPs are described as vaccines against SARS‐CoV‐2. The spike protein subunit S1 or epitopes from S and M proteins (SM) plus/minus the nucleocapsid protein (N) are selected as antigens to either coat BPs during assembly inside engineered Escherichia coli or BPs are engineered to specifically ligate glycosylated spike protein (S1‐ICC) produced by using baculovirus expression in insect cell culture (ICC). BP vaccines are safe and immunogenic in mice. BP vaccines, SM‐BP‐N and S1‐ICC‐BP induced protective immunity in the hamster SARS‐CoV‐2 infection model as shown by reduction of virus titers up to viral clearance in lungs post infection. The BP platform offers the possibility for rapid design and cost‐effective large‐scale manufacture of ambient temperature stable and globally available vaccines to combat the coronavirus disease 2019 (COVID‐19) pandemic. Abstract : Ambient temperature stable, scalable coronavirus disease 2019 polymer particle vaccines are developed by engineering bacterial cell factories to assemble biopolymer particles either directly coated with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antigens or to capture soluble spike protein S1 subunit produced by an insect culture. Polymer particle vaccines induce protective immunity in a hamster SARS‐CoV‐2 infection model reducing virus titers up to viral clearance in lungs post infection.